2012
DOI: 10.1055/s-0032-1329962
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Design Study to Assess the Bioequivalence of Generic and Branded Hydroxychloroquine Sulfate Tablets in Healthy Volunteers

Abstract: Hydroxychloroquine (HCQ) is a racemic 4-aminoquinoline derivative that was first introduced as an antimalarial, and subsequently applied to the treatment of autoimmune diseases such as rheumatoid arthritis and systemic lupus erythematosus. Information on the pharmacokinetics of HCQ in healthy volunteers, especially in a Chinese population is limited, and this study was conducted to provide support for a generic product to obtain marketing authorization in China.The aim of the present study was to compare the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…A previous study reported a C max of 199.0 ng/mL, while in this trial the C max of the T preparation was 238.9 ng/mL 18 . The PK data of this trial were slightly higher than those of previous studies, indicating that our bioavailability of hydroxychloroquine T is better than the previous studies.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…A previous study reported a C max of 199.0 ng/mL, while in this trial the C max of the T preparation was 238.9 ng/mL 18 . The PK data of this trial were slightly higher than those of previous studies, indicating that our bioavailability of hydroxychloroquine T is better than the previous studies.…”
Section: Discussioncontrasting
confidence: 68%
“…13 A previous parallel-designed fasting trial that was consistent with our research design, did not better evaluate the impact on food on the bioavailability of hydroxychloroquine in comparison with the study with a crossover study design 13 ; however, it (54 healthy subjects) had a smaller sample size than ours, and the sex ratio was unknown. 13,18 A previous study reported a C max of 199.0 ng/mL, while in this trial the C max of the T preparation was 238.9 ng/mL. 18 The PK data of this trial were slightly higher than those of previous studies, indicating that our bioavailability of hydroxychloroquine T is better than the previous studies.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Also, we estimated the point estimation of the geometric mean ratio (GMR) and its 90%CI (30 mg:60 mg dapoxetine). For 90%CI within the 80% to 125% range, the dapoxetine pharmacokinetics was considered dose proportional 11–14 . The Wilcoxon rank‐sum test was used to compare t max values between the treatment groups.…”
Section: Methodsmentioning
confidence: 99%